Leptospirosis among returned travelers : a GeoSentinel site survey and multicenter analysis—1997–2016 - de Vries, Sophia G. (2018)
Leptospirosis is a potentially fatal emerging zoonosis with worldwide distribution and a broad range of clinical presentations and exposure risks. It typically affects vulnerable populations in (sub)tropical countries but is increasingly reported in travelers as well. Diagnostic methods are cumbersome and require further improvement. Here, we describe leptospirosis among travelers presenting to the GeoSentinel Global Surveillance Network. We performed a descriptive analysis of leptospirosis cases reported in GeoSentinel from January 1997 through December 2016. We included 180 travelers with leptospirosis (mostly male; 74%; mostly tourists; 81%). The most frequent region of infection was Southeast Asia (52%); the most common source countries were Thailand (N = 52), Costa Rica (N = 13), Indonesia, and Laos (N = 11 each). Fifty-nine percent were hospitalized; one fatality was reported. We also distributed a supplemental survey to GeoSentinel sites to assess clinical and diagnostic practices. Of 56 GeoSentinel sites, three-quarters responded to the survey. Leptospirosis was reported to have been most frequently considered in febrile travelers with hepatic and renal abnormalities and a history of freshwater exposure. Serology was the most commonly used diagnostic method, although convalescent samples were reported to have been collected infrequently. Within GeoSentinel, leptospirosis was diagnosed mostly among international tourists and caused serious illness. Clinical suspicion and diagnostic workup among surveyed GeoSentinel clinicians were mainly triggered by a classical presentation and exposure history, possibly resulting in underdiagnosis. Suboptimal usage of available diagnostic methods may have resulted in additional missed, or misdiagnosed, cases.